Accelerating the magnetic island by the modulated resonant magnetic perturbation for the disruption avoidance on J-TEXT. (1st October 2022) - Li, Da; Wang, Nengchao; Ding, Yonghua; Yu, Qingquan; Li, Mao; Hu, Qiming; He, Ying; Mao, Feiyue; Shen, Chengshuo; Jia, Ruo; Huang, Zhuo; Zhou, Song; et al.
Abstract: The acceleration of the magnetic island rotation by the modulated resonant magnetic perturbation (MRMP) has been studied in J-TEXT tokamak experiments. After applying the MRMP, the phase difference between the tearing mode (TM) and MRMP, Δ ξ, oscillated near the effective phase difference, Δ ξ eff, which was defined as the time averaged value of Δ ξ . When the Δ ξ eff was closed to the— π /2, the MRMP only contributed an accelerating torque on the TM. As the result, the TM rotation frequency was increased by a few kilohertz for the optimized relative phase by small RMPs of the order of 10 −5 of the toroidal field and the locked mode induced disruption was avoided. It is found that the TM rotation could be increased to a higher frequency by applying a stronger MRMP. There is a negative sinusoidal relationship between TM frequency and Δ ξ eff .